Divide and conquer: the FTAA, U.S. trade strategies and public services in the Americas - Sinclair, Scott; Traynor, Ken (Ferney-Voltaire, 2004)
"In this paper, Sinclair and Traynor argue that the services and investment rules of the proposed Free Trade Area of the Americas Treaty (FTAA) present a grave threat to public services and public interest regulation throughout the Americas. They base their analysis on the neo-liberal philosophy that the smallest government is best government; they contend the FTAA would create intense pressure to privatize, deregulate, and erode existing public services.